Marriage, Sex, and Civic Culture in Late Medieval London - McSheffrey, Shannon (Book collections on Project MUSE., 2006)
Using extensive evidence from archival documents from both the ecclesiastical court system and the records of city and royal government, as well as advice manuals, chronicles, moral tales, and liturgical texts, McSheffrey examines how marital and sexual relationships were woven into the fabric of late medieval London.